A SEMA3E mutant resistant to cleavage by furins (UNCL-SEMA3E) inhibits choroidal neovascularization. (December 2016) - Toledano, Shira; Lu, Huayi; Palacio, Agustina; Kigel, Boaz; Kessler, Ofra; Allon, Gilad; Barak, Yoreh; Neufeld, Gera; Schaal, Shlomit
Abstract: Abnormal subretinal choroidal neovascularization (CNV) is a major cause of blindness in exudative age-related macular degeneration (AMD). Current anti-angiogenic treatments by VEGF sequestering agents have been successful, but a significant proportion of patients do not respond well to these treatments, and the response of others diminishes over time, suggesting that additional anti-angiogenic agents that function by separate mechanisms may be of use to such patients. We have previously found that a point mutated form of semaphorin-3E resistant to cleavage by furin like pro-protein convertases (UNCL-Sema3E) displays potent anti-angiogenic properties. We therefore determined if UNCL-Sema3E has potential as an inhibitor of CNV formation. We chose to study UNCL-Sema3E rather than wild type sema3E because unlike full length sema3E, the major p61-Sema3E peptide that is produced by cleavage of sema3E with furin like pro-protein convertases activates signal transduction mediated by the ErbB2 receptor and can promote tumor metastasis in addition to its anti-angiogenic activity. UNCL-Sema3E inhibited efficiently vascular endothelial growth factor-A (VEGF), platelet derived growth factor (PDGF) and basic fibroblast growth factor (bFGF) signaling in human umbilical vein derived endothelial cells (HUVEC) and to a lesser extent hepatocyte growth factor (HGF) signal transduction. CNV that was induced in the eyes of C57 black mice by laser photocoagulation was inhibited by 65% (P < 0.01) following a single bolus intra-vitreal injection of 5 μg UNCL-Sema3E. This inhibitory effect was similar to the inhibition produced by a single bolus intra-vitreal injection of 5 μg aflibercept. A similar inhibition of CNV was observed following the injection of UNCL-Sema3E into the eyes of Long-Evans rats. However, a higher dose of UNCL-Sema3E (125 μg), partially due to the larger volume of the vitreous cavity of rats, was required to achieve maximal inhibition of CNV. Injection of UNCL-Sema3E into eyes of healthy mice did not have any adverse effect on retinal function as assessed by optic kinetic reflex (OKR) or by electroretinogram (ERG) assays nor did UNCL-Sema3E injection affect the structure of the retina as determined using histology. To conclude, our results suggest that UNCL-Sema3E may be useful for the treatment of exudative AMD, which does not respond well to conventional anti-VEGF therapy. Highlights: Point mutated Sema3E resistant to furin cleavage inhibits CNV as well as aflibercept. The point mutated sema3E does not affect visual acuity or retinal function by itself. The point mutated sema3E inhibit signaling induced by VEGF, PDGF and bFGF. The mechanism by which it inhibits VEGF does not rely on sequestration of VEGF. The point mutated sema3E may benefit AMD patients refractory to currently used drugs.